An Unusual Case of Anti-GBM Antibody Elevation in HIV-Associated Nephropathy - Vinay Minocha; Raafat Makary; Andreea Poenariu (Case Reports in Nephrology)
Introduction. The most commonly seen glomerular disease in HIV infected patients is HIV-associated nephropathy (HIVAN); however, a multitude of other nephropathies can occur in HIV infection with an almost equal cumulative frequency. We report an unusual case of a patient with clinical and histological evidence of HIVAN in which the diagnosis was initially confounded by the finding of an elevated serum anti-glomerular basement membrane (anti-GBM) antibody. Case Presentation. We present a case of a 27-year-old African American female with a history of schizophrenia, cocaine abuse, and HIV infection who upon admission to our hospital was found to have severe acute kidney injury requiring hemodialysis. Urine studies revealed nephrotic range proteinuria and a serological workup was positive for anti-GBM antibody elevation with a value of 91 units (normal: 0–20 units). A renal biopsy revealed HIVAN with no evidence of crescentic glomerulonephritis or anti-GBM disease. Conclusion. This case highlights the need for careful interpretation of anti-GBM antibody tests in HIV infected patients with kidney disease and, in particular, the need for biopsy confirmation of the diagnosis prior to starting therapy. More research is needed to study the prognostic correlation between the degree of anti-GBM antibody elevation in HIVAN and disease severity.